Urinary proteomic pattern in female stress urinary incontinence: a pilot study. Issue 11 (November 2016) - Koch, Marianne; Mitulovic, Goran; Hanzal, Engelbert; Umek, Wolfgang; Seyfert, Sonja; Mohr, Thomas; Koelbl, Heinz; Laterza, Rosa
Abstract Introduction and hypothesis Previous studies aiming to identify specific pre-defined urine protein biomarkers for stress urinary incontinence (SUI) have not identified clinically important differences. The hypothesis of our study was that the global distribution of urinary proteins, the proteome, differs between women with and those without SUI. Methods In this age-matched case–control study, we compared the urinary proteome of 20 women with SUI and 20 controls. Proteins were identified by applying high-performance liquid chromatography separation and tandem mass spectrometry detection. Data analysis was performed using Mascot 2.4.1 embedded in ProteinScape 3.1. Results We identified 828 different proteins. The concentration of six of those showed a significant difference between urine samples of SUI patients and those of controls (q value < 0.25). Four proteins showed a higher abundance in SUI samples compared with controls: plasma serine protease inhibitor (logFC 1.11), leucine-rich alpha-2-glycoprotein (logFC 3.91), lysosomal alpha-glucosidase (logFC 1.24), and peptidyl-prolyl cis- trans isomerase A (logFC 1.96). We identified two proteins in lower abundance in SUI samples compared with controls: uromodulin (logFC −4.87) and TALPID3 (logFC −1.99). Conclusions Overexpression of plasma serine protease inhibitor, leucine-rich alpha-2-glycoprotein, lysosomal alpha-glucosidase, and peptidyl-prolyl cis- trans isomerase A, and lower expression of uromodulin and TALPID3, in urine may be associated with female SUI.